Perbandingan Pengaturan Yurisdiksi Universal dalam Hukum Indonesia dengan Hukum Jerman - Dendi Saputra; Asep Suherman (GLOBAL SCIENTS PUBLISHER, 2026)
The ICC’s failure to bring international criminals to justice has become a serious issue of impunity, necessitating the activation of universal jurisdiction mechanisms. This qualitative study aims to compare the regulations on universal jurisdiction in German and Indonesian law in order to improve these regulations in Indonesia. This study employs a legal and conceptual approach, utilizing a literature review method to collect legal materials; the findings are analyzed and compared to generate innovative improvements to these jurisdictional regulations in Indonesia. The findings indicate that Indonesia should adopt several prinsiples as regulated by German law. Consequently, it is important for legislators to revise the National Criminal Code or enact specific regulations on universal jurisdiction that are more comprehensive.